PENGARUH MANAJEMEN LABA DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE: TAX AVOIDANCE - Rafi Ahmad; Euis Nessia Fitri (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
This research aims to analyze and determine the influence of earnings management and transfer pricing on tax avoidance in primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2023. The method used in this study is a quantitative approach, utilizing secondary data from the financial statements of primary consumer goods sector companies listed on the IDX for the period 2018-2023. The research sample was selected using purposive sampling method, resulting in 21 companies that met the selection criteria. The results of the study indicate that the earnings management variable has a positive effect on tax avoidance, while transfer pricing has a positive effect on tax avoidance. These findings suggest that earnings management can reduce the tax avoidance efforts made by companies. This may be due to the fact that companies engaging in earnings management tend to be more transparent in their financial reports, thereby reducing the likelihood of tax avoidance. On the other hand, transfer pricing has been proven to have a positive influence on tax avoidance. This indicates that companies using transfer pricing strategies tend to be more active in seeking ways to reduce their tax liabilities. Transfer pricing is often used to shift income to jurisdictions with lower taxes, thereby increasing the potential for tax avoidance Keywords: Earnings Management, Transfer Pricing, and Tax Avoidance.